Influence of the constraint-induced method of constraint-induced movement therapy on improving lower limb outcomes after stroke: A meta-analysis review - Zhang, Jing; Feng, Hongsheng; Lin, Jinpeng; Zhai, Hua; Shen, Xia (Frontiers in Neurology, 2023)
Abstract Background: Constraint-induced movement therapy (CIMT) targeting lower limb function uses various methods. The influence of CIMT methods on lower limb outcomes after stroke has rarely been examined. Objectives: This study aimed to examine CIMT effects on lower limb outcomes and explore the influence of CIMT methods on treatment effects after stroke, with other potential factors considered as covariates. Methods: PubMed, Web of Science, Cochrane Library, Academic Search Premier via EBCOHost, and PEDro databases were searched until September 2022. We included randomized control trials with CIMT targeting lower limb function and dosage-matched active control. The Cochrane risk-of-bias tool was used to evaluate the methodological quality of each study. Hedges’g was used to quantify CIMT’s effect size on outcomes compared to active control. Meta-analyses were conducted across all studies. A mixed-variable meta-regression analysis was used to investigate the influence of CIMT methods on treatment effects after stroke, with other potential factors considered as covariates. Results: Twelve eligible randomized control trials with CIMT were included in the meta-analysis, ten trials with low risk of bias. A total of 341 stroke participants were involved. For the treatment effects on lower limb function, CIMT showed moderate short-term effect size (Hedges’ g=0.567; P<.05; 95% confidence interval [CI]: 0.203-0.931), but a small and insignificant effect size (Hedges’ g =0.470; P>.05; 95%CI: -0.173 to 1.112), compared with conventional treatment. The CIMT method using weight strapped around the non-paretic leg and ICF outcome category of movement function were identified as significant factors contributing to the heterogeneity of short-term effect sizes across studies (β= -0.854 and 1.064 respectively, R2=98%, P<.05). Using weight strapped around the non-paretic leg had a significant contribution to the heterogeneity of long-term effect sizes across studies as well (β= -1.000, R2=77%, P<.05). Conclusion: CIMT is superior than conventional treatment in improvement of lower limb function in short-term but not long-term. CIMT method using weight strapped around a non-paretic leg contributed negatively to treatment effect, might be not recommended.